Characterization of Azotobacter vinelandii deoxyribonucleic acid and folded chromosomes. - Sadoff, H L (1979)
The properties of Azotobacter vinelandii deoxyribonucleic acid (DNA) and folded chromosomes were studied and compared to those of Escherichia coli as a standard. Based on melting temperature and buoyant density measurements, the guanosine + cytosine content of purified A. vinelandii DNA was 65%, whereas that of E. coli DNA was 50%. The results of renaturation studies showed that the unique DNA sequence lengths of the two organisms were similar with Cot1/2 values of 7.3 +/- 0.4 mol.s/liter and 7.5 +/- 0.3 mol.s/liter, respectively, for A. vinelandii and E. coli. Folded chromosomes of A. vinelandii sedimented in a centrifugal field at a rate identical to those derived from E. coli, 1,600 to 1,700S. Based on the DNA content per cell and the mass of a single genome, A. vinelandii contains at least 40 chromosomes per cell.